2019
DOI: 10.1002/jbm4.10125
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Dormancy and Reactivation in Bone: Skeletal Biology and Therapeutic Opportunities

Abstract: In the advanced stages of many cancers, tumor cells disseminate from the primary site and colonize distant locations such as the skeleton. These disseminated tumor cells colonizing bone can evade treatments and survive for prolonged periods in a dormant state before becoming reactivated to form overt metastases. The precise interactions between tumor cells and the bone microenvironment that promote survival, dormancy, and reactivation are currently unknown; as a result, bone metastases remain incurable. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 121 publications
0
24
0
Order By: Relevance
“…Giancotti provided a hypothesis in his review that presumes that the epithelial-mesenchymal transition (EMT) might be a possibility for reactivation from dormancy [88]. A review by Byrne et al summarizes that castration causes bone loss and increased metastasis via hypoxia induction and vascular remodeling [89]. Furthermore, Miftakhova et al reported that cyclin A1 coupled with aromatase (CYP19A1) enables PCa metastatic growth in bone marrow through manipulating androgen concentrations in the TME [90].…”
Section: Pca Homingmentioning
confidence: 99%
See 1 more Smart Citation
“…Giancotti provided a hypothesis in his review that presumes that the epithelial-mesenchymal transition (EMT) might be a possibility for reactivation from dormancy [88]. A review by Byrne et al summarizes that castration causes bone loss and increased metastasis via hypoxia induction and vascular remodeling [89]. Furthermore, Miftakhova et al reported that cyclin A1 coupled with aromatase (CYP19A1) enables PCa metastatic growth in bone marrow through manipulating androgen concentrations in the TME [90].…”
Section: Pca Homingmentioning
confidence: 99%
“…The dynamics of Wnt and Ras at each stage of PCa metastasis need to be clarified, and the details within each stage must be elucidated, in order to completely answer the question. Byne et al have reviewed that castration-mediated osteoporosis might link to PCa BM which bone reformation might increase BM activity [89]. Detail mechanism regarding castration-mediated osteoporosis is not well-known but recent knowledge indicates that Wnt signaling is involved in osteoblast activity instead of osteoclast activity [163].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Different approaches have been proposed in order to resolve the biologic complexity underlying the pathophysiologic step to bone dissemination. The first of the steps in the process of cancer spreading to the bone is the homing to the marrow microenvironment throughout the bloodstream of the tumor cells, via the neo-angiogenesis process, trough permissive bone marrow endothelial cells [33,34]. Remarkably, a prone microenvironment is involved in the cancer cycle, educating and hijacking the tumor niche that is to be colonized throughout a neoplastic permissive environment [35,36].…”
Section: Cancer Cell Homing To the Bone Marrow: Bridging The Gap Bmentioning
confidence: 99%
“…The bone marrow is likely the most common site where cellular dormancy occurs, since many of the mechanisms that are thought to keep cancer cells dormant, are based on molecular pathways that are usually used by haematopoietic stem cells for maintaining their own quiescence [167,168,170,172]. Undoubtedly, cellular dormancy is an extremely complex phenomenon, that reflects the complexity of the bone marrow microenvironment and the many niches that reside there.…”
Section: Tumour Cellular Dormancymentioning
confidence: 99%